International Financial Integration through the Law of One Price - Levy Yeyati, Eduardo (World Bank, Washington, DC, 2012)
The authors argue that the cross-market premium (the ratio between the domestic and the international market price of cross-listed stocks) provides a valuable measure of international financial integration, reflecting accurately the factors that segment markets and inhibit price arbitrage. Applying to equity markets recent methodological developments in the purchasing power parity literature, they show that nonlinear Threshold Autoregressive (TAR) models properly capture the behavior of the cross market premium. The estimates reveal the presence of narrow non-arbitrage bands and indicate that price differences outside these bands are rapidly arbitraged away, much faster than what has been documented for good markets. Moreover, the authors find that financial integration increases with market liquidity. Capital controls, when binding, contribute to segment financial markets by widening the non-arbitrage bands and making price disparities more persistent. Crisis episodes are associated with higher volatility, rather than by more persistent deviations from the law of one price.